187 Novel thienopyridines are potent anti-platelet drugs, inhibiting platelet activation, aggregation and showing synergy with aspirin. (5th June 2017) - Binsaleh, Naif; A. Wigley, Catherine; A. Whitehead, Kathryn; Moreno-Martinez, Daniel; Daniels, Sarah; Jones, Sarah; Rensburg, Michelle van; Pilkington, Lisa; Barker, David; Dempsey-Hibbert, Nina
Abstract : Background: Management of Acute Coronary Syndromes (ACS) often involves the use of platelet inhibitors. The most commonly used drug, clopidogrel, belongs to a class of thienopyridine molecules which targets the P2Y12 receptor on platelets and it is commonly used in combination with the COX-1 inhibitor acetylsalicylic acid (ASA). However, the effect of these treatments is variable amongst patients, highlighting a need for a refinement of this class of P2Y12 inhibitor. The aim of this study was to assess the efficacy of six novel thienopyridine derivatives synthesised by our group by examining their potential as in-vitro inhibitors of platelet function. Methods: Healthy human platelets were isolated and incubated with novel thienopyridine compounds (DJ0081, DJ0199, DJ0021, DJ0206, DJ0171, DJ0097) (10 µM, 30 min) prior to stimulation with ADP (10µM) and analysis of alpha granule secretion (CD62P expression), GPIIbIIIa activation (PAC1 expression) and platelet leukocyte aggregate (PLA) formation using flow cytometry. Furthermore, light transmission aggregometry (LTA) was used to assess ADP-stimulated aggregation after these treatments. Synergy with ASA (30 µM) was also analysed by LTA following incubation with ASA and thienopyridine. All results were compared to ADP-stimulated samples and samples treated with clopidogrel (10 µM, 30 min) prior to ADP stimulation. Results: All six novel compounds demonstrated a significant reduction in ADP-mediated platelet aggregation (p<0.001), CD62P expression (p<0.001), PAC1 expression (p<0.01) and PLA formation (p<0.05). These compounds were also shown to enhance the inhibitory effects of ASA. DJ0171 and DJ0199 were particularly potent, displaying greater inhibitory effect than clopidogrel. Conclusion: The study demonstrates the potential for new thienopyridine compounds as modulators of platelet function and points to the possibility of future use in patients at risk of platelet hyperactivity and thrombosis.